From Nomad to Nobody - Buckley, Michael (Canada, 2011)
A documentary about the vanishing nomads of Tibet. The documentary is a personal take on the plight of Tibetan nomads. The film was shot on location in Tibet and in northern India. Tibetan nomads are being forcibly relocated by Chinese officials-shifted off their traditional grazing lands into concrete ghettos, where they are marginalized and have little chance of making a decent living, or finding a new profession. Previously, when grazing yaks, they were self-sufficient and lived in an entirely sustainable way. Now, they are unemployed, and dependent on the Chinese government for hand-outs-and for food. This re-settlement policy is designed to wipe out nomad culture and its strong connections to traditional Tibetan values.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films